JAMUR BERACUN DALAM KARYA GRAFIS - MASRISA HIDAYU, Drs. Ariusmedi, M.Sn (Serupa The Journal of Art Education, 2019)
This Final Project aims to visualize the type of poisonous mushrooms through lino cut. This final  project is expected to increase the public’s insight into the type of poisonous mushrooms, and  remind the public to be more careful in consuming mushrooms. The method in making this final  project through several stages, namely: (1) Preparation, (2) Elaboration, (3) Synthesis, (4)  Realization of concepts, and (5) finishing, then exhibited in the form of exhibitions. This Final Project consists of ten with the title: The Devil, Lystac Oysterling, Fly Agari, Bloody Brittlegil, Death Cap,  Pixies Parasol, Jack O’Lantern, Galerina Marginata, Surpise Webcap, dan Angel Wing.Key Words: Poisonous Mushrooms, Graphic Arts, Lino Cut